The Lead Lag Relationship between Spot and Futures Markets in The Energy Sector - Chen, Jeng-Chung Victor; Prince, Yolanda Gabriela; Ha, Quang An (International Journal of Energy Economics and Policy, 2017)
This paper investigates the lead-lag relationship between spot and futures markets of the most representative energy sources under three different scenarios using the Vector Error Correction Model. Additionally, a ratio of speed of adjustment was built in order to establish the market contribution of both spot and futures markets on price innovation. The empirical findings indicate an important leadership and contribution of futures market in relation to price discovery regardless of oil shocks, business cycle and transaction costs. Nevertheless, an improvement in spot markets' contribution to price discovery is observed during recession periods rather than expansion periods. Keywords: Future price, Spot price, Price discovery, Lead Lag Relationship, Energy JEL Classification: G13